Improved electro‐geometric model for shielding failure analysis of transmission lines. Issue 4 (1st July 2018) - Hashemian, Pejman; Vahidi, Behrooz; Rahiminezhad, Abolfazl
Abstract : An improved electro‐geometric model (EGM) based on upward corona leader system consideration is introduced. The proposed method is a modified version of EGM and its high accurate results are independent of the height, voltage level, and circuit type of structure. The equations of the proposed method are modified by means of genetic algorithm based on the leader progression models (LPM) results which are consistent with the experimental results. To evaluate the performance of the proposed method, the shielding failure rates (SFR) of a single‐circuit transmission line with different protection angles are calculated and compared to those of LPM and a revised EGM. The comparisons show that the results of the improved method roughly agree with the results of LPM. To ensure about the performance of the proposed method, it is applied on ten different practical structures with different characteristics. The results of IEGM are compared to the field data and the results of the revised EGM. The comparisons demonstrate that the proposed IEGM is an appropriate method for SFR calculation irregardless of the height, voltage level, and circuit type. In other words, the proposed IEGM is as simple as conventional EGM and as accurate as LPM.